2020
DOI: 10.1136/bmjqs-2020-011405
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, nature and causes of avoidable significant harm in primary care in England: retrospective case note review

Abstract: ObjectiveTo estimate the incidence of avoidable significant harm in primary care in England; describe and classify the associated patient safety incidents and generate suggestions to mitigate risks of ameliorable factors contributing to the incidents.DesignRetrospective case note review. Patients with significant health problems were identified and clinical judgements were made on avoidability and severity of harm. Factors contributing to avoidable harm were identified and recorded.SettingPrimary care.Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 27 publications
(38 reference statements)
1
41
1
17
Order By: Relevance
“…Participants' reports of limited and inconsistent quality assurance processes in inhours general practice were in-keeping with other studies 9,17,18 and set in the context of evidence of a substantial burden of preventable patient harm in English primary care. 5 Whilst our study has indicated the potential of CG to support an increasingly multidisciplinary primary care workforce to practise to its full potential, our findings also reflect the need to ensure such interventions do not become another stressor for a workforce dealing with a challenging and rising workload. 19 The impact of audit and feedback on clinician practice and patient outcomes Consultation peer-review interventions such as CG are a form of clinical audit.…”
Section: Quality Assurance In General Practicementioning
confidence: 64%
See 1 more Smart Citation
“…Participants' reports of limited and inconsistent quality assurance processes in inhours general practice were in-keeping with other studies 9,17,18 and set in the context of evidence of a substantial burden of preventable patient harm in English primary care. 5 Whilst our study has indicated the potential of CG to support an increasingly multidisciplinary primary care workforce to practise to its full potential, our findings also reflect the need to ensure such interventions do not become another stressor for a workforce dealing with a challenging and rising workload. 19 The impact of audit and feedback on clinician practice and patient outcomes Consultation peer-review interventions such as CG are a form of clinical audit.…”
Section: Quality Assurance In General Practicementioning
confidence: 64%
“…2 Within primary care internationally there is evidence of significant variation in clinician practice 3 and a substantial burden of preventable harm. 4,5 However, determining the extent to which observed variation is unwarranted and potentially harmful to patients is challenging, and requires detailed assessment of the clinician-patient interaction. 6 Systems to identify and minimise unwarranted variation in individual clinician practice are increasingly relevant in the context of trends towards more multidisciplinary clinical workforces.…”
Section: Introductionmentioning
confidence: 99%
“… 3 While some incidents, such as unexpected complications during the provision of correct care, are not preventable, others, such as failure to recognise serious illness or patient deterioration, can contribute to avoidable harm. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Around 2% to 3% of all primary care encounters result in a patient safety incident, with 1 in 25 causing a serious harm outcomes [3]. These incidents are frequently related to diagnosis (either delayed or missed) or to treatment (delayed or inappropriate) [4,5]. A number of different factors contribute to these incidents, such as the working environment, information transfer at the primary-secondary interface, doctor-patient relationship or continuing education [6][7][8].…”
Section: Introductionmentioning
confidence: 99%